Control features within the rplJL-rpoBC transcription unit of Escherichia coli. - Barry, G (1979)
Gene fusions constructed in vitro have been used to examine transcription regulatory signals from the operon which encodes ribosomal proteins L10 and L7/12 and the RNA polymerase beta and beta' subunits (the rplJL-rpoBC operon). Portions of this operon, which were obtained by in vitro deletions, have been placed between the ara promoter and the lacZ gene in the gene-fusion plasmid pMC81 developed by M. Casadaban and S. Cohen. The effect of the inserted DNA segment on the expression of the lacZ gene (in the presence and absence of arabinose) permits the localization of regulatory signals to discrete regions of the rplJL-rpoBC operon. An element that reduces the level of distal gene expression to one-sixth is located on a fragment which spans the rplL-rpoB intercistronic region. This strongly supports the idea that there is an attenuator in this region. The terminator for the operon is located on a fragment which spans the 3' end of the rpoC gene. The major promoter for the operon precedes the rplJ gene [Yamamoto, M. & Nomura, M. (1978) Proc. Natl. Acad. Sci. USA 75, 3891-3895 and Linn, T. & Scaife, J. (1978) Nature (London) 276, 33-37] and was not examined in this study. However, a weak promoter is observed on the fragment that spans the rplJ-rplL intercistronic region. Other regions of the operon may also contain weak promoters. The contribution of these elements to the regulation of this complex operon is discussed.